DNMT3B Functions: Novel Insights From Human Disease - Gagliardi, Miriam; Strazzullo, Maria; Matarazzo, Maria R. (Frontiers in Cell and Developmental Biology, 2018)
DNA methylation plays important roles in gene expression regulation and chromatin structure. Its proper establishment and maintenance are essential for mammalian development and cellular differentiation. DNMT3B is the major de novo DNA methyltransferase expressed and active during the early stage of embryonic development, including implantation. In addition to its well-established role to methylate repetitive sequence at centromeric and pericentromeric regions, recent findings suggest that DNMT3B shapes intragenic CpG-methylation of highly expressed genes. Although largely studied, much remains unknown regarding how these specific patterns of de novo DNA methylation are established in human cells, and which are the mechanisms that guide recruitment and activity of DNMT3B in vivo. Many evidence suggest that DNMT3B recruitment is regulated by numerous mechanisms including chromatin modifications, presence of DNA-binding factors, transcription levels and non-coding RNAs. Disruption of DNA methylation patterns is a common feature of human diseases with chromosomal and genomic instabilities, including inherited disease and cancer. Hypomorphic mutations in DNMT3B lead to the rare autosomal recessive ICF (Immunodeficiency, Centromeric instability and Facial anomalies) syndrome, type I, while the altered expression of this methyltransferase has been associated with development of various cancers. In both cases it implies abnormal DNA hypomethylation and hypermethylation patterns affecting gene expression and genomic architecture. We will provide an overview of the intense research of the last few years aimed at deciphering the molecular mechanisms by which DNA methylation abnormalities are associated to the onset and progression of these pathologies.